ANALYSIS OF THE OPTIMAL LOCATION OF TABANAN DISTRICT TO SUPPORT THE DEVELOPMENT OF A FOOD LOGISTIC CENTER - Ocky Soelistyo Pribadi; Adrianto Sugiarto Wiyono; Ni Made Nanda Pradnya Swari; Ni Luh Gede Novi Jayanti; Novan Rachmadi Atmaja (Politeknik APP Jakarta, 2022)
The development of a Food Logistics Center in Tabanan Regency needs to be supported by determining the optimal location, namely the most accessible area for both achievement and the ease of distributing food products to other locations. For that purpose, the analytical method use in this research is